PENGELOLAAN FASILITAS UTAMA DI DESTINASI WISATA TAMAN MARGASATWA DAN BUDAYA KINANTAN KOTA BUKITTINGGI - Andriko, Rivaldo; Yulia, Nur Arini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the condition and management of the main facilities at Kinantan Wildlife and Cultural Park (TMSBK) in Bukittinggi City, which combines a zoo with elements of Minangkabau culture and history through the Wildlife Park, Fort de Kock Fortress, and Limpapeh Bridge. The research uses a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The results show that most facilities are still functioning well and attract visitors, but challenges remain, such as the lack of information boards and weak supervision and maintenance. Management includes aspects of planning, organizing, actuating, and controlling, but has not been optimal. Improving facility quality and sustainable planning is needed for TMSBK to grow as an educational, recreational, and sustainable tourist destination. Keywords: facility management, TMSBK, Bukittinggi tourism, tourist destination, conservation